2023
DOI: 10.1021/acs.jafc.3c02930
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Review of Self-Assembled Food Protein-Derived Multicomponent Peptides: From Forming Mechanism and Structural Diversity to Applications

Abstract: Food protein-derived multicomponent peptides (FPDMPs) are a natural blend of numerous peptides with various bioactivities and multiple active sites that can assume several energetically favorable conformations in solutions. The remarkable structural characteristics and functional attributes of FPDMPs make them promising codelivery carriers that can coassemble with different bioactive ingredients to induce multidimensional structures, such as fibrils, nanotubes, and nanospheres, thereby producing specific healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
16
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 107 publications
0
16
0
Order By: Relevance
“…Food-derived natural peptides with abundant bioactivities have been widely studied in the field of food. , Recently, researchers have found that food-derived natural peptides with remarkable structural and functional characteristics could self-assemble into multidimensional structures to thereby produce specific health benefits . Marques et al showed that cowpea peptides could self-assemble into micelle structures with impressive antioxidant activity through measurements of oxygen radical absorption capacity.…”
Section: Self-assembling Peptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Food-derived natural peptides with abundant bioactivities have been widely studied in the field of food. , Recently, researchers have found that food-derived natural peptides with remarkable structural and functional characteristics could self-assemble into multidimensional structures to thereby produce specific health benefits . Marques et al showed that cowpea peptides could self-assemble into micelle structures with impressive antioxidant activity through measurements of oxygen radical absorption capacity.…”
Section: Self-assembling Peptidesmentioning
confidence: 99%
“…In recent years, researchers have reviewed the synergies of various noncovalent interactions involved in the self-assembly process, , which are necessary to determine thermodynamically stable structures. In fact, individual amino acids such as Phe or Ser can form oligomers, clusters, or even toxic fiber aggregates in solution with various noncovalent interactions, which hints at the mechanism of peptide assembly and growth trends .…”
Section: Regulatory Mechanisms Of Self-assembling Peptidesmentioning
confidence: 99%
“…The self-assembly of metabolites results in the spontaneous formation of an ordered nanostructure guided by thermodynamics and dynamics. 48 In the self-assembly process, noncovalent interactions, including hydrophobic interactions, hydrogen bonding, π−π stacking, and electrostatic interactions, cause the monomers to spontaneously assemble into a stable structure with a specific regular geometric appearance (Figure 2). 49 These noncovalent interactions can affect the structures and functions of the assemblies, even though they are weak.…”
mentioning
confidence: 99%
“…Electrostatic interactions refer to the force generated by the interaction of electric charges, including electrostatic attraction and repulsion, which are nondirectional and have a low binding energy. 48 These interactions are essential for maintaining the structural stability of biomolecules and realizing biological functions. Because of the weak acid and base properties of the COOH and NH 2 , the pH of the solution can be adjusted to affect the electrostatic interactions.…”
mentioning
confidence: 99%
See 1 more Smart Citation